THE INFLUENCE OF THE RECRUITMENT AND SELECTION PROCESS ON EMPLOYEE PERFORMANCE PT KIARA SAWIT ABADI 1 - Mira Udina; Netty Laura; Emerald G. M Tobing (Universitas Kristen Indonesia, 2024)
Palm oil plantation companies are encountering intense competition in the global market. To effectively engage in this competition, PT Kiara Sawit Abadi must ensure that employee performance is at its peak to realize its business objectives. The recruitment process conducted by PT Kiara Sawit Abadi have a positive impactt on employe performancee. This is evident from the significance level of 0.005, which is below 0.05, and the calculate t-value of 2.924, surpassing the t-table valuee of 1.676. Consequently, it can be inferred that the recruitmen proces afects the performancee of employes at PT Kiara Sawit Abadi. Similarly, the selection process administered by PT Kiara Sawit Abadi also significantly and positively influences employee performance. This is demonstrated by the significance level of 0.003, lower than 0.05, and the calculate t-valuee of 3.087, exceding the t-table value of 1.676. Thus, it can be deduced that the selection process impacts employee performance at PT Kiara Sawit Abadi. The combined recruitmen and selectio process exert a positiv and notable influenced on employe performanced at PT Kiara Abadi. This is substantiated by the F Test results, indicating a significancee valu of 0.001 < 0.05. Employee performance at PT Kiara Sawit Abadi is influenced by the recruitment process by 55.3% and selection by 56.1%. In conclusion, the variable of selection holds the highest influence on employee performance at PT Kiara Sawit Abadi. PT Kiara Sawit Abadi is encouraged to enhance both the employee recruitment and training process and the selection process to enhance the productivity of its employees. Keywords: Recruitment, Selection, Employee Performance